2018
DOI: 10.1002/jcb.26681
|View full text |Cite
|
Sign up to set email alerts
|

Berberine demonstrates anti‐inflammatory properties in Helicobacter pylori‐infected mice with chronic gastritis by attenuating the Th17 response triggered by the B cell‐activating factor

Abstract: Berberine (BBR) is an isoquinoline alkaloid derived from various medicinal herbs. Previous studies have suggested that BBR exerts antimicrobial, antitumor, and antidiabetic effects and can be used to treat Helicobacter pylori-induced chronic gastritis. However, the exact mechanism by which BBR inhibits H. pylori infection is not fully understood. We investigated the anti-inflammatory properties and potential mechanism of BBR in H. pylori-infected mice with chronic gastritis. We found that BBR can suppress the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Metformin (MET) has been used as the first‐line drug therapy for T2DM, due to its excellent inhibitory effect on hepatic glucose production . Berberine (BB) is an isoquinoline alkaloid originally isolated from Chinese herb Coptis chinensis (Huang lian), which exerts anti‐diabetic and anti‐inflammatory activities . Over the past decades, a number of experimental and clinical studies have been centralized on the biological activities of Metformin, Berberin and their derivatives .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin (MET) has been used as the first‐line drug therapy for T2DM, due to its excellent inhibitory effect on hepatic glucose production . Berberine (BB) is an isoquinoline alkaloid originally isolated from Chinese herb Coptis chinensis (Huang lian), which exerts anti‐diabetic and anti‐inflammatory activities . Over the past decades, a number of experimental and clinical studies have been centralized on the biological activities of Metformin, Berberin and their derivatives .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Berberine (BB) is an isoquinoline alkaloid originally isolated from Chinese herb Coptis chinensis (Huang lian), which exerts anti-diabetic [13][14][15][16] and anti-inflammatory activities. [17][18][19] Over the past decades, a number of experimental and clinical studies have been centralized on the biological activities of Metformin, Berberin and their derivatives. [20][21][22][23][24][25][26][27] However, little information is available on the synthesis of novel compounds containing Metformin and Berberin derivatives.…”
mentioning
confidence: 99%
“…Studies of TCM on H. pylori have shown that some herbs such as R. coptidis, C. phellodendri, and berberine can inhibit H. pylori (Li et al, 2016). Many clinical trials have also shown that berberine, an antimicrobial, antidiabetic, anti-inflammatory, and antitumor drug can be used to treat H. pylori-induced chronic gastritis in vitro and in vivo (Chang et al, 2011;Lin et al, 2015;Tan et al, 2017;Wu et al, 2018). Furthermore, an open-label randomized phase IV trial showed that both bismuth-containing and berberinecontaining quadruple therapy achieved the recommended efficacy and can be recommended as the first-line treatment for H. pylori eradication in Xi'an, China (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As an "Eastern antibiotic" in TCM, berberine has been used to treat diarrhea for a thousand years (Zhang, 1992). Recently, many experiments have proved that berberine has anti-H. pylori ability in vivo and in vitro (Huang et al, 2015;Wu et al, 2018). Berberine can effectively suppress multiresistant strains of H. pylori, and the minimum H. pylori inhibitory concentration of amoxicillin and tetracycline was lowered after the berberine intervention in vitro (Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation